Hispanic-serving HBCUs: towards an anti-colonial meso-relevant theory of organizational identity in sacred spaces of Black education - Dwuana Bradley; Gina Tillis (Frontiers in Education)
IntroductionThis study addresses demographic changes at HBCUs and proposes an anti-colonial organizational framework for Historically Black emerging Hispanic Serving Institutions (HB-eHSIs, also referred to as Hispanic-serving HBCUs) to support both Black and Brown students while preserving the historic mission of HBCUs.MethodsWe use qualitative methodology and rely on 45–60 minute semi-structured interviews with 15 faculty and administrators from three Historically Black emerging HSIs in Texas to develop the proposed organizational framework.ResultsFindings are highlighted through four key tenets, each operationalized based on themes from extant literature and the practices and organizational logics of Black and Brown faculty and staff at HBeHSIs: 1. Tending to white settler colonialism, 2. Tending to fiscal precarity, 3. Tending to sacred spaces, 4. Tending to fallacious notions of essentialism.DiscussionThe proposed framework aims to foster solidarity between Black and Brown students and challenge oppressive systems through a radically inclusive approach to serving both communities. Recommendations include reexamining leadership structures, forming coalitions, and creating consortiums to support HBCUs’ evolving needs and diverse student populations. Findings also emphasize the need for dual federal designation for HB-eHSIs to secure funding and legitimacy.